A 3D Visual Tool for Analyzing Changes in Hair Volume and Length Caused by Medications - Kim, Jong‐Hyun; Lee, Jung; Kwon, Seungbin; Jo, Minji; Hwang, Yunjin; An, In‐Sook (Computer animation and virtual worlds, 2025)
ABSTRACT This paper proposes a 3D visual tool based on physically‐based simulation to verify and analyze changes in the volume and length of hair after treatment with cosmetics or other chemicals. Unlike fur and hair simulations in virtual environments, real hair undergoes various chemical treatments not only to enhance hair quality but also to increase hair density. Such treatments are important as they lead to hairstyling, which significantly affects a person's impression. We propose a novel visual tool that visualizes and analyzes changes in the length and volume of original strands before and after chemical treatment based on physically‐based hair simulation. The results are applied to various scenarios, including back hair volume, root hair volume, side hair volume, crown hair volume, and hair sagging, to evaluate its effectiveness. Changes in Hair Length and Volume Caused by Drug Treatment.